Exploiting multiple-frequency bursting of a shape memory oscillator. (May 2022) - Zhang, Xiaofang; Li, Hongqing; Jiang, Wenan; Chen, Liqun; Bi, Qinsheng
Abstract: In this paper we explored a novel multiple-frequency bursting of a shape memory oscillator under parametrically and externally excitation. Based on the fast-slow dynamics analysis method, the one-parameter bifurcation curves under different frequency ratios are proposed for some specific parameters. The corresponding jumping phenomenon are verified via transformed phase, and the multi-valued characteristic are observed by the domain of attraction. The results express that the multiple-frequency oscillation can induce complex bursting phenomenon. In addition, the jump multi-value phenomena of tristability are more abundant than bistability and monostability.